(3GdJQHjI GdGLJeGYjI ddCHfGA hGdBHGA (B:s (3GdJQHjI GdLSejI(B-(3GdJQHjI GdYbdjI(B-(3GdJQHjI GdYbGFOjI(B-(3GdJQHjI GdQhMjI(B-(3GdJQHjI GdCNdGbjI(B-(3GdJQHjI GdGLJeGYjI(B-(3GdJQHjI GdfaSjI(B-(3GdJQHjI GdEQGOjI(B-(3GdJQHjI GdLfSjI(B-(3GdJQHjI GdLeGdjI (B/s - (3GdbGVj, SYjO ESeGYjds ((3GdbGgQI (B:s (3YGde GdcJH,s, 2015)
(3jJfGhd cJGH (B((3GdJQHjI GdGLJeGYjI ddCHfGA hGdBHGA (B: (3GdJQHjI GdLSejI(B-(3GdJQHjI GdYbdjI(B-(3GdJQHjI GdYbGFOjI(B-(3GdJQHjI GdQhMjI(B-(3GdJQHjI GdCNdGbjI(B-(3GdJQHjI GdGLJeGYjI(B-(3GdJQHjI GdfaSjI(B-(3GdJQHjI GdEQGOjI(B-(3GdJQHjI GdLfSjI(B-(3GdJQHjI GdLeGdjI(B) (3hGdPj bGe HJCdjag (B((3SYjO ESeGYjd GdbGVj(B) (3aj MhGdj (B(423) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdCSQI aj GdESdGe(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdaUd GdChd (B: (3GdJQHjI GdRhGLjI OGFQI GdRhLjI, GdaUd GdKGfj (B: (3GdJQHjI GdCSQjI hMbhb GdCHfGA hGdBHGA, GdaUd GdKGdK (B: (3GdJQHjI GdbQGHjI hMbhb GdCQMGe, GdaUd GdQGHY (B: (3GdJQHjI GdLhGQjI hMbhb GdLhGQ, GdaUd GdNGeS (B: (3GdJQHjI GdhWfjI hMbhb GdehGWfI(B.s
(3HHdjhLQGajI (B: (3UaMI (B419-423.s
Keywords: (3GdCSQI aj GdESdGes; (3GdESdGe hYde GdGLJeGY GdJQHhjs; (3GdBHGA hGdCHfGAs -- (3LhGfH OjfjIs